Strategi akun @dr_kamilinjamilin_official dalam Menyampaikan Hadis tentang Etika Menjaga Privasi di Instagram: Analisis Konten dan Respon Pengikut - Mukhammad Alfani; Farichatul Fauziyah (Al-Hasyimi: Jurnal Ilmu Hadis, 2024)
This article analyzes the strategy of the Instagram account @dr_kamilinjamilin_official in conveying hadith about the ethics of maintaining privacy on social media. Using the netnography method, this study explores interactions in cyberspace and analyzes the video content uploaded by Dr. Kamilin Jamilin. The account utilizes visual and storytelling approaches to make the hadith more interesting and relevant to the younger generation. Active interaction with followers and consistency in content uploading are key to successful message delivery. The hadith emphasizes the importance of respecting others' personal boundaries, in line with Islamic ethical values. The content on this account was well received by followers, who showed support for the message. The article also highlights the importance of maintaining ethics and the value of brotherhood in Islam as well as the negative impact of sharing personal information on social media. Cases such as Vivi, a victim of the ITE Law for spreading disgrace, serve as a clear example of the consequences of such injustice. This research emphasizes the role of social media as an effective and ethical da'wah platform, especially if supported by good digital literacy. The @dr_kamilinjamilin_official account is an example of how social media can be used to remind Muslims to be wiser and more responsible in the media. A relevant and religious values-based approach shows the great potential of social media in building ethical awareness amidst the challenges of the digital era.